Justice Pauline Davis Hanson Retirement Luncheon at TorNino's - Watkins, Howard::::::::: (1987)
Fresno County Bar Association President Howard Watkins presenting Justice Hanson one of the volumes of all of her published appellate court opinions-a gift from Fresno County Bar Association Judy Soley behind lectern, Mary Louise Frampton, and ? On far right